Veterinary medicinal product regulation in sub-Saharan Africa: identifying barriers and opportunities for enhancing VMP regulatory systems - Pyatt, Alison Z.; Eckford, Suzanne; Joseph, Noel; Borriello, S. Peter; Oyati, Osi (Frontiers in Veterinary Science, 2025)
Effective regulation of veterinary medicines is essential to ensure veterinarians and animal keepers have access to assured quality, safe and effective products to prevent and treat animal disease. The maturity of national veterinary medicine regulatory systems varies between countries across sub–Saharan Africa and immature systems disincentivise manufacturers from bringing products to these markets. Common barriers to regulatory system strengthening identified by national regulatory agencies (NRAs) in the region include lack of financial resources, lack of trained personnel, and a need for suitable IT platforms to enable work-sharing and sharing of confidential data. Greater convergence and harmonisation of regulatory systems would enable more efficient use of resources through facilitation of regional NRA collaborations. Development of internationally agreed standards and guidance on good regulatory practice, a global regulators forum for exchange of best practice, and application of a self-assessment or audit tool, all of which exist for human medicines regulation, would enable NRAs for veterinary medicines to create and implement institutional development plans to achieve system strengthening. Independent assurance of NRA maturity would enhance opportunity for inter-agency reliance or unilateral recognition of regulatory decisions on product authorisation and good manufacturing practice inspection, currently under-utilised pragmatic approaches to ensuring necessary medicines are available quickly.